Organic Matter and Root Development of Soybean in Agroforestry Soils tropical Sub Watershed Bengawan Solo Wonogiri Indonesia - Supriyadi Supriyadi; Djoko Purnomo; Yuxand Devano Mangkulla (Faculty of Agriculture, Universitas Sebelas Maret, 2017)
Alfisols is a soil that lack of organic matter (OM). thus making the physical properties of the soil is easily damaged, because OM is used as an adhesive on soil physical properties. This study aimed to examine the physical properties of Alfisols in agroforestry based of teak and its effect on the development of soybean. This research used a Randomized Block Complete Design (RBDC) which consists of three factors (soybean varieties, teak litter dose and NPK chemical fertilizers. The results showed that Alfisols in agroforestry based on teak relative good with the stability of the aggregate value of the 225,101 (Very Steady). Varieties and increasing teak litter doses affect soybean root development while NPK fertilizer did not make an impact. Argo Mulyo varieties have better root development in comparison with Grobogan, and litter dose of 2,5 Mg ha-1 has the best root development in each variety.